APPLICATION OF TERRITORIAL ACCESSIBILITY METHODOLOGIES TO COMPARE AND UNDERSTAND THE DIFFERENCES IN EQUITY CONDITIONS BETWEEN TWO NEIGHBORHOODS OF DIFFERENT SOCIOECONOMIC STRATA IN A COLOMBIAN INTERMEDIATE CITY - Diego Alexander ESCOBAR; Fernando José BELEÑO; Carlos Alberto MONCADA (Geo Journal of Tourism and Geosites)
The number of opportunities in a specific area significantly influences the planning, development, and zoning of city neighborhoods. In this study, a methodological approach was employed to analyze pedestrian accessibility between two neighborhoods of varying strata in Manizales, Colombia. The research utilized the ArcGIS program, yielding results that highlighted disparities in service access and opportunities between the neighborhoods. It was concluded that higher strata neighborhoods offer greater amenities to residents, emphasizing the need to reconsider urban planning strategies.